The impact of macroeconomic factors on Malaysian Government bond yields 10 year / Erra Shaziera Mohd Rashul - Mohd Rashul, Erra Shaziera (Faculty of Business and Management, 2019)
A government bond is a debt security issued by a government to support government spending. Before investing in government bonds, investors need to assess several risks associated with the country, such as country risk, political risk, inflation risk and interest rate risk, although the government usually has low credit risk. Government bonds are considered risk-free and are traded in highly liquid markets. Government bond yields is the return on investment, expressed as a percentage, on the government's debt obligations. On the downside, government bonds return is typically low rate of return. Thus, the purpose of this study is to identify whether macroeconomic factor has an impact on government bond yields in Malaysia. Dependent variable is the government bond yields. The independent variables are inflation rate, interest rate, GDP, stock market volatility and unemployment rate. The study conducted by using time series data analysis. Data collected is on the quarterly basis. There are 32 observation with the period of study between 2010 QI until 2017 Q4 that derived from Thomson Reuters DataStream. We apply ordinary least square (OLS) method which is multiple regression analysis. The result showed the GDP, interest rates, stock market volatility and unemployment rate are positive significant towards Malaysia government bond yields10 years while the inflation rate showed positive insignificant towards Malaysia government bond yields-IO years.